Evaluasi Kesesuaian Obat Dengan Kartu Stok Di Puskesmas Gondomanan Kota Yogyakarta - Titami, Arina; Andriani, Yuni; Saputra, Doni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: The proper storage and distribution of drugs is very important to ensure the effects of drugs in the body and all drugs should be stored in the right storage place. Improper drug storage can cause damage to drugs that can endanger patients and health services themselves. Objective: This study aims to evaluate drug storage, specifically the accuracy of data on the number of drugs on the stock card, at the Gondomanan Primary Health Center in Yogyakarta. Method: The research was conducted using a descriptive observational approach with a cross-sectional design. Data were collected using a checklist referring to Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016 and Petunjuk Teknis Standar Pelayanan Kefarmasiaan di Puskesmas Tahun 2019. Result: The accuracy of data on the number of drugs on the stock card at the Gondomanan Primary Health Center in Yogyakarta is 100%. Conclusion: The accuracy of data on the number of drugs on the stock card at the Gondomanan Primary Health Center in Yogyakarta is by standards based on Peraturan Pemerintah Kesehatan Republik Indonesia Nomor 74 Tahun 2016 and Petunjuk Teknis Standar Pelayanan Kefarmasiaan di Puskesmas Tahun 2019.